The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/00365513.2013.773064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of OneTouch Verio®, a new blood glucose self-monitoring system for patients with diabetes

Abstract: The OneTouch Verio(®) displayed sufficient analytical quality and satisfactory user-friendliness. It is suitable for point-of-care testing of blood glucose concentration when handled by patients and healthcare professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Certainly, enhancement in treatment satisfaction may play a critical role in increasing patient self-efficacy and commitment to therapy, thereby supporting in reaching long-term stable glycemic control, in addition to the minimization of the risk of diabetic complications [18]. More recently, diabetes technology has extended, and studies reported that technological improvements in glucometers are enhanced diabetes management and patient satisfaction [19,[23][24][25]. In this present study, we explored whether the smartLIGHT™ based BGM can impact the clinical characteristics and GMS in T2D patients over a period of time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, enhancement in treatment satisfaction may play a critical role in increasing patient self-efficacy and commitment to therapy, thereby supporting in reaching long-term stable glycemic control, in addition to the minimization of the risk of diabetic complications [18]. More recently, diabetes technology has extended, and studies reported that technological improvements in glucometers are enhanced diabetes management and patient satisfaction [19,[23][24][25]. In this present study, we explored whether the smartLIGHT™ based BGM can impact the clinical characteristics and GMS in T2D patients over a period of time.…”
Section: Discussionmentioning
confidence: 99%
“…It is well demonstrated that diabetes technology has expanded. Studies reported that technological improvements in glucometers, including SmartLIGHT™ glucometers, improve diabetes management and patient satisfaction due to on-screen glucose range information using a color range indicator [6,19,[23][24][25]27]. Studies also reported that a blood glucose meter that provides automatic on-screen glucose range information using a color range indicator significantly improved the ability of patients having T2D to classify blood glucose readings into low range, in the range, or high glycemic range [6].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, each woman is told to download an app to record blood sugar. This app allows both patients and diabetologist to keep connected by exchanging text messages (short message service SMS) or progress reports via email [6].…”
Section: Discussionmentioning
confidence: 99%
“…The other three systems showed slightly better accuracy results for study personnel measurements compared to lay-user measurements. Different studies showed that accuracy achieved by trained study personnel is often better than accuracy achieved by lay-persons [ 11 , 12 , 26 , 27 ]; however, only few user performance evaluations were performed on the basis of procedures described in ISO 15197:2013 [ 25 , 26 , 28 30 ].…”
Section: Discussionmentioning
confidence: 99%